The Extent of Gaining Loyalty and Belongingness among Students in the 9th and 10th Grades who Involved in The National Summer Project (BASMA) of Public Schools: A Case Study of Southern District of Mazar Schools for 2017/2018 - SOULAYMANE NAWAISEH, Najah Ibrahim (Journal of Human Sciences, 2020)
This study aims at identifying the extent to which students in grades 9th and 10th have achieved loyalty and belonging values by involving them in the national project (BASMA), which is implemented by Ministry of Education in comparison with the same values acquired before participation in the national project. The project has been supervised by the Directorate of Education / Southern Al-Mazar. One thousand two hundred participants; a questionnaire was designed and given by hand to this sample. This questionnaire consisted of three dimensions of the project implementation: national dimension, family dimension, social dimension). Results of the study showed that all the dimensions represented had shown improvements compared with attitude for the same sample participating in the project, but the relative importance for all paragraphs differed. We recommend that all projects similar to this need to be supported and motivated; students who were involved should take part in such a case for the future activities plans.